2021
DOI: 10.22271/maths.2021.v6.i1a.636
|View full text |Cite
|
Sign up to set email alerts
|

Multiple comparison test by Tukey’s honestly significant difference (HSD): Do the confident level control type I error

Abstract: Examining a huge amount of data is a typical issue in any research process. However, different statistical processes and techniques play essential role to derive a meaningful conclusion from the presented enormous data. Control of type I error is highly essential for a researcher or statistician while dealing with comparisons test with more than two variables. Multiple testing statistical tests provides a structural system and minimizes the error rate by helping to derive meaningful accurate conclusions. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…The Moderna vaccine had the highest average sentiment score of 0.0551, with 71 tweets in China. The Analysis of Variance (ANOVA) [ 46 ] and Tukey (CI = 95%) [ 47 ] methods were used to examine differences in the sentiments of these five countries. These methods showed that India and China, the USA and China, Canada and China, and the UK and China had differences of 0.2061, 0.1816, 0.0805, and 0.2031 in sentiments related to the Covaxin vaccine, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Moderna vaccine had the highest average sentiment score of 0.0551, with 71 tweets in China. The Analysis of Variance (ANOVA) [ 46 ] and Tukey (CI = 95%) [ 47 ] methods were used to examine differences in the sentiments of these five countries. These methods showed that India and China, the USA and China, Canada and China, and the UK and China had differences of 0.2061, 0.1816, 0.0805, and 0.2031 in sentiments related to the Covaxin vaccine, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For normality tests, Kolmogorov-Smirnov and Shapiro-Wilk tests [82] were applied. The data were evaluated by a one-way ANOVA [83], and the differences among means were tested using the Tukey HSD test [84].…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis was performed by IBM SPSS Statistics 25 (Armonk, NY, USA) software. Kolmogorov-Smirnov and Shapiro-Wilk tests [118] were used for data normality test and, the results were investigated by one-way ANOVA [119], the means were compared by Tukey HSD test [120]. Significance was marked by using lower case letters (a, b, c, and d) in the manuscript.…”
Section: Discussionmentioning
confidence: 99%